Critical Discourse Analysis of Gender Representation in Grade Seven English Language Subject in The Ministry of Education in Afghanistan - Nazimi, Sayed Zahir; Hatifi, Kamran (Integrated Journal for Research in Arts and Humanities, 2023)
The present investigation of gender representation in English textbooks in the Afghanistan context uses critical discourse analysis. The data were collected from the content of the school texts book that was taught to seven grade English language learners. The research used Fairclough’s (1995) three-dimensional framework to analyze the data. Variables like women and men's social and domestic roles, visibility of females and males, females and males’ activities, females and males’ semantic roles, and pictorial representation were analyzed to make clear hidden sides of inequalities or power misbalance between men and women. The finding of this study displayed that the seven grade textbooks were discriminated in favor of males in definite roles of activities. For instance, men occupied the role of prayer, engineer, and pilot, shepherded more than women. The study also showed that the textbook displayed bias between women and men in terms of pictorial, representation visibility, and some activities roles in which men had the upper hand. The result also depicted that there existed stereotypical roles and activities associated with males and females in these books men and women were presented with bias in terms of social status, power, and dominance. In other words, there was significant discrimination and anti-feminism in the analyzed textbooks.